Blended Learning: Blended Resources – a Collaborative Approach to Supporting Students - Freeman, Margaret; Parker, Lyn (Proceedings of the International Conference on Networked Learning, 2004)
This paper describes the ongoing process of action research and collaboration between an academic and a librarian, as we have explored how electronic resources can interact with, influence and change teaching and learning opportunities. From our experiences in this project, we identify the factors that have influenced the effective integration of learning resources with the programme of learning opportunities. As well as knowledge of, and access to, the technology and the resources, it is argued that active dialogue between the librarian, the academic and the students is a major influencing factor in developing effective and appropriate blended learning solutions.